2016
DOI: 10.18632/oncotarget.7007
|View full text |Cite
|
Sign up to set email alerts
|

IL-32θ inhibits stemness and epithelial-mesenchymal transition of cancer stem cellsviathe STAT3 pathway in colon cancer

Abstract: Interleukin (IL)-32 is a well-known cytokine associated with inflammation, virus infections and cancer. IL-32θ is a newly identified isoform of IL-32, whose function has yet to be elucidated. In this study, we investigated IL-32θ function in colon cancer stem cells. Using samples from colon cancer patients, we found that the expression of IL-32θ mRNAs was significantly suppressed in tumor regions. We investigated the effects of IL-32θ on colon cancer. Ectopic expression of IL-32θ attenuated invasion, migration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 36 publications
2
38
0
Order By: Relevance
“…Colon cancer is among the most common cancers worldwide, and it is the second leading cause of cancer-related deaths. 19 One evidences showed ENO1 expressed aberrantly in multiple tumor types and its expression was associated with disease progression. 11,20,21 However, little is known about the role and mechanism of ENO1 in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Colon cancer is among the most common cancers worldwide, and it is the second leading cause of cancer-related deaths. 19 One evidences showed ENO1 expressed aberrantly in multiple tumor types and its expression was associated with disease progression. 11,20,21 However, little is known about the role and mechanism of ENO1 in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, much research focus has been on trying to understand inflammatory responses within the tumours through tumour interactions with the extracellular matrix, mesenchymal stem cells, immune cells, cancerassociated fibroblasts and tumour-activated macrophages (Criscitiello et al, 2014;Gilkes et al, 2014;Ginestier et al, 2010Ginestier et al, , 2011Li et al, 2012;Lu et al, 2014). A crosstalk between CSCs and their microenvironment via certain cytokines has been demonstrated (Bak et al, 2016;Di Stefano et al, 2010;Sansone et al, 2007;Singh et al, 2013). In 2011, Liu and coworkers reported that BCSCs are regulated by cytokine-related signalling pathways and highlighted the influence IL6 and IL8 production to maintain CSC properties Sansone et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The driving force of colorectal cancer was recognized as cancer stem cells (CSCs) (O Brien, Pollett, Gallinger, et al, ), which are a small population of cells in solid tumor responsible for the initiation and progression of cancer (Khan et al, ). CSCs were first identified in acute myeloid leukemia and have been found in various types of cancer (Bak, Kwon, Bak, et al, ). Besides, CSCs are considered to be the most crucial factors that contribute to drug resistance, relapse, and metastasis (Visvader & Lindeman, ).…”
Section: Introductionmentioning
confidence: 99%